Detection of L-Proline-Catalyzed Michael Addition Reaction in Model Biomembrane. (26th February 2019) - Hirose, Masanori; Sugisaki, Shigenori; Suga, Keishi; Umakoshi, Hiroshi
Abstract : A method to detect the L-proline- (L-Pro-) catalyzed Michael addition reaction in model biomembranes has been established, using N -[ p (2-benzimidazolyl)phenyl]maleimide and acetone as reactants. The effect of liposome membranes on this reaction was kinetically analyzed using fluorescence spectroscopy. The kinetics of the reaction were different from those of the constituent lipids of the liposomes. Zwitterionic 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine liposome, which is in the solid-ordered phase, had a better value of reaction rate, suggesting that the reaction rate constants of this reaction in liposome membrane systems could be regulated by the characteristics of the liposome membrane (i.e., the phase state and surface charge). Based on the results obtained, a plausible model of the L-Pro-catalyzed Michael addition reaction was discussed. The obtained results provide us with an easily detectable method to assess the reactivity of L-Pro in biological systems.